Family-based brand equity in the hospitality industry - Dębski, Maciej; Górska-Warsewicz, Hanna; Skalska, Teresa (Kapitał marki bazujący na rodzinnym charakterze przedsiębiorstwa w sektorze usług noclegowych, 2019)
The competitiveness of family-owned companies providing accommodation services is an important factor securing their operations. Among the characteristic features of the family-owned companies are: hospitality, the quality of the services provided and the relations between the guest and the owner which are based on mutual trust. Empirical research in the form of CAWI was carried out between 2017-2018 and covered 83 owners of family-owned businesses. The authors analysed 23 elements characterising the brand of family- owned businesses, including a recognisable logo and name, the quality of the services, trust, openness to guests’ needs. The particular aim of the research was to answer the question of the perception of a brand’s importance among the owners of such companies. The results showed that in their opinion, the brand is responsible for identifying and distinguishing the company, helping to create the company’s image, retaining regular clients and gaining new guests. At the same time, it secures the company’s growth by improving its market power, providing its competitive advantage and generating additional income
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 161-175